Naskah Tafsir Al-Qur’an Candi Cangkuang - Dadang Darmawan; Irma Riyani (Lajnah Pentashihan Mushaf Al-Qur'an, 2019)
The study of religious manuscript is important task to do to preserve the ancient intellectual sources of Muslim scholars in Indonesia. Religious manuscripts have been found in many different areas in Indonesia including Qur’anic manuscript. However, among others, Qur’anic and Tafsir manuscripts are the least to be discovered. Several researchers have reported that only a few Qur’anic manuscripts discovered. Among this limited discovery is Candi Cangkuang Qur’anic and tafsir manuscript founded in Garut, West Java. This research attempts to examine Candi Cangkuang Qur’anic and tafsir manuscript. Particular attention is given to investigate its origin, contents and structures of the manuscript. This research employs qualitative method to find out socio-historical background of the manuscript. This research shows that Candi Cangkuang Qur’anic manuscript was brought out to Garut by Arif Muhammad from his home town in Central Java, around South coastal area known as Muria region, as shown in its language used in this manuscript. This manuscript can be categorized as tafsir lughowi as the author wrote it word-by-word explanation. This type of tafsir is resemblance with tafsir al-Jalālayn that popular in Indonesian pesantren. The Qur’anic text is written in naskh script, while its tafsir in riq’ah script. Keywords:Al-Qur’an; Candi Cangkuang; historical; manuscript; tafsir